Borneosabahia Franz is a junior synonym of Elacatophora Schaufuss (Coleoptera, Scydmaenidae, Cyrtoscydmini, Cephenniini) - Jałoszyński, Paweł (Zootaxa, 2008)
Based on examination of the holotype of Elacatophora robusta Schaufuss, the monotypic genus Elacatophora Schaufuss is transferred from Cephenniini to Cyrtoscydmini. Borneosabahia Franz is placed as a junior synonym of Elacatophora, which results in six new combinations: Elacatophora apion (Jałoszyński), E. dissimilis (Jałoszyński), E. javanica (Jałoszyński), E. longipes (Jałoszyński), E. malaysiae (Franz), and E. maxima (Jałoszyński). Elacatophora robusta is illustrated, and identification key to the genera of Oriental Cyrtoscydmini is provided.